Antibiotics in fetal and early life and subsequent childhood asthma: nationwide population based study with sibling analysis. (28th November 2014) - Örtqvist, Anne K; Lundholm, Cecilia; Kieler, Helle; Ludvigsson, Jonas F; Fall, Tove; Ye, Weimin; Almqvist, Catarina
Abstract : Objective To investigate the association between exposure to antibiotics in fetal and early life and asthma in childhood, with adjustment for confounding factors. Design Nationwide prospective population based cohort study, including sibling control design. Setting Swedish population identified from national demographic and health registers. Participants 493 785 children born 2006-10; 180 894 of these were eligible for sibling analyses. Main outcome measure Asthma defined as having both an asthma diagnosis and dispensed asthma drugs. The association between antibiotic exposure and asthma was investigated in the whole cohort with Cox proportional hazard regression. A stratified proportional hazards model conditional on sibling group was used to adjust for shared factors within families. Confounding by respiratory infections was assessed by investigating whether specific groups of antibiotics were associated with asthma. Results Antibiotic exposure in fetal life was associated with an increased risk of asthma in cohort analyses (hazard ratio 1.28, 95% confidence interval 1.25 to 1.32), but not in sibling analyses (0.99, 0.92 to 1.07). In cohort analyses, antibiotics used to treat respiratory infections in childhood were associated with a more pronounced increased risk of asthma (4.12, 3.78 to 4.50) than antibiotics used for urinary tract and skin infections (1.54, 1.24 to 1.92). In sibling analyses, the excess risks after exposure to antibiotics for respiratory infections decreased (2.36, 1.78 to 3.13) and disappeared for antibiotics for urinary tract and skin (0.85, 0.47 to 1.55). Conclusions Previous positive associations between exposure to antibiotics in fetal and early life and subsequent childhood asthma could have been caused by confounding by shared familial factors, in addition to confounding by respiratory infections.